PEER OBSERVATION AS A PROFESSIONAL DEVELOPMENT STRATEGY TO RAISE TEACHERS' SELF-DRIVE IN IMPROVING THEIR TEACHING SKILLS IN A LANGUAGE CENTER - Nanda Octavia; Wina Hartaty (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2026)
This study investigates the effectiveness of a peer observation program as a professional development tool in a language center. The research explores teachers’ perceptions of the program, its role in fostering self-awareness and professional growth, and the challenges encountered during its implementation. As an evaluation of an implemented program within an educational institution, this study employed a qualitative case study design. Data were collected through questionnaires distributed to 14 part-time teachers participating in the program. The findings reveal that peer observation contributed positively to teachers’ professional development by encouraging self-reflection through feedback, constructive criticism, insightful questions, and peer suggestions. Collaborative activities within the program also helped teachers identify their strengths, weaknesses, and areas for improvement in teaching practice. Overall, 58% of the teachers responded positively to the program. However, several challenges limited the program’s effectiveness, including scheduling conflicts, unclear procedures, limited confidence in giving and receiving feedback, and resistance to peer evaluation. The study highlights the importance of clear communication, structured procedures, and institutional support in implementing an effective peer observation program. It also suggests that peer observation can become a meaningful and sustainable professional development practice when supported by reflective dialogue, collegial trust, and consistent follow-up activities.